Accelerated telomere shortening in adrenal zona reticularis in patients with prolonged critical illness - Nonaka, Keisuke; Takubo, Kaiyo; Aida, Junko; Watai, Yoriko; Komatsu, Akiko; Gomi, Fujiya; Shichi, Yuuki; Yamazaki, Yuto; Ishiwata, Toshiyuki; Sasano, Hironobu; Arai, Tomio (Frontiers in Endocrinology, 2023)
Background: The number of patients with prolonged critical illness (PCI) has been increasing in many countries, and the adrenal gland plays an important role in maintaining homeostasis during PCI. Chronic disease burden is reportedly associated with shorter telomere lengths in human tissues. However, the association between PCI and telomere lengths in human adrenal cells is poorly understood. Methods: This study examined near-normal adrenal glands obtained from 14 autopsied patients who died suddenly (control group) and lipid-depleted adrenal glands obtained from 18 autopsied patients who died after PCI (PCI group). By using quantitative fluorescence in situ hybridization, relative telomere lengths (RTLs) were determined in the parenchymal cells of the three adrenocortical zones (zona glomerulosa, zona fasciculata, and zona reticularis [ZR]) and in the chromaffin cells of the medulla. The number of adrenal parenchymal cells was determined by immunohistochemistry and digital image analysis. Results: RTLs in ZR cells were significantly shorter in the PCI group than in the control group for both men and women (P = 0.0001 for men and P = 0.0012 for women). However, RTLs in the remaining three types of adrenal cells did not differ between the control and PCI groups for both men and women. The number of ZR cells was higher in the PCI group than in the control group for both men and women (P < 0.0001 for both men and women). The proportion of the number of ZR cells to the total number of adrenocortical parenchymal cells was also higher in the PCI group than in the control group (P < 0.0001 for both men and women). The Ki-67 proliferation index in ZR cells was higher in the PCI group than in the control group (P = 0.0039 for men and P = 0.0063 for women). Conclusions: This study demonstrated ZR cell-specific telomere shortening in patients with adrenal lipid depletion who died after PCI. Our results suggest that the reactive proliferation of ZR cells accelerates the telomere shortening and aging process in ZR cells in these patients. The results of our study may contribute to the understanding of adrenal aging during PCI.